2016
DOI: 10.3945/ajcn.116.136879
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and weight loss: a systematic review and meta-analysis of randomized and nonrandomized controlled weight-loss trials

Abstract: Our results indicate that vitamin D status may be marginally improved with weight loss in comparison with weight maintenance under similar conditions of supplemental vitamin D intake. Although additional studies in unsupplemented individuals are needed to confirm these findings, our results support the view that the association between obesity and lower serum 25-hydroxyvitamin D may be due to reversed causation with increased adiposity leading to suboptimal concentrations of circulating vitamin D. This trial w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 51 publications
2
45
0
3
Order By: Relevance
“…Our findings also indicate that, in the short term, vitamin D 3 supplementation had no additional effect on the magnitude of weight loss compared to placebo, which agrees with previous evidence that vitamin D 3 supplementation does not promote improvements in the degree of obesity [52]. On the other hand, we also observed that weight loss obtained without Vitamin D 3 supplementation did not modify circulating 25(OH)Vit D levels, which agrees with the inference that loss of adipose tissue does not promote the release of 25(OH)Vit D release from fat into the bloodstream [53].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings also indicate that, in the short term, vitamin D 3 supplementation had no additional effect on the magnitude of weight loss compared to placebo, which agrees with previous evidence that vitamin D 3 supplementation does not promote improvements in the degree of obesity [52]. On the other hand, we also observed that weight loss obtained without Vitamin D 3 supplementation did not modify circulating 25(OH)Vit D levels, which agrees with the inference that loss of adipose tissue does not promote the release of 25(OH)Vit D release from fat into the bloodstream [53].…”
Section: Discussionsupporting
confidence: 91%
“…However, the percentage of baseline weight loss that is mandatory for a significant effect on vitamin D levels has varied between 5% and >10% [46, 49] and Mallard et al report no clear dose-response as part of a meta-analysis of weight loss vs weight maintenance among vitamin D-supplemented individuals [53]. …”
Section: Diet-induced Weight Loss and Vitamin Dmentioning
confidence: 99%
“…As vitamin D is fat‐soluble it has been suggested that a greater storage in fatty tissue decreases bioavailability in obese individuals . Theoretically, loss of fat mass could increase vitamin D levels in the circulation . Therefore an increase in circulating vitamin D could be a marker of improved metabolic health during lifestyle intervention.…”
Section: Introductionmentioning
confidence: 99%
“…14 Theoretically, loss of fat mass could increase vitamin D levels in the circulation. 15,16 Therefore an increase in circulating vitamin D could be a marker of improved metabolic health during lifestyle intervention.…”
mentioning
confidence: 99%